IMPLEMENT DIRECT TORQUE AND FLUX CONTROL (DTC) INDUCTION MOTOR DRIVE MODEL: A REVIEW - Subbamma, Dr. Manne Rama; Sindhuja, Mrs. B.; Vijayalakshmi, Rudru; Chandrikareddy, Chintalappagari (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2020)
Direct torque control ( DTC ) is considered one of the modern control methods, which wildly used in industrial variable speed drive systems to govern behaviors of induction motors. The main objective of this paper is to introduce a comprehensive study of a conventional direct torque of three phase induction motors. Moreover, the paper also aims to enhance and improve the transient response of the conventional DTC by proposing a novel design of its switching table, which considered as an essential component of DTC control circuit. At first, Space Vector theory was implemented to derive a mathematical model of a threephase induction motor. Second, the model was simulated by using Matlab Simulink software due to its simplicity. The conventional DTC and proposed DTC were applied on the computer model of the motor at no-load and when the motor shaft is loaded respectively. It was observed from the results that the transient response of the proposed DTC is better than the response of the conventional one. The paper concluded with number of important results, which obtained from the computer model of the two DTC control methods. Ripple